2001
DOI: 10.1046/j.1365-246x.2001.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep crustal structure in central India using magnetotelluric studies

Abstract: SUMMAR YMagnetotelluric studies over the Damoh±Jabalpur±Mandla±Anjaneya pro®le in central India have delineated Vindhyan sediments which are about 5 km thick in the Damoh± Katangi region. The crust below the Vindhyan sediments shows the characteristics of lower crust, as observed from the relatively lower resistivity of about 200 V m and high seismic velocities (P-wave velocities of 6.5 km s x1 compared with 5.8±6.2 km s x1 in the surrounding region). It is conjectured that the upper crust may have been comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
4
26
0
Order By: Relevance
“…A similar low-resistive upper crustal structure near the Narmada river was also observed in the present study. Similarly, the MT model used here and earlier MT model reported by Gokarn et al (2001) both found deep crustal conductors (C1 and C2 in Fig. 5(a)).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…A similar low-resistive upper crustal structure near the Narmada river was also observed in the present study. Similarly, the MT model used here and earlier MT model reported by Gokarn et al (2001) both found deep crustal conductors (C1 and C2 in Fig. 5(a)).…”
Section: Discussionsupporting
confidence: 80%
“…Other regions show gravity lows ranging from −20 to −50 mgal. Several similarities between the results obtained using this MT model and those from earlier gravity, seismic (Tewari and Kumar, 2003), and MT models (Gokarn et al, 2001) are discussed in the following section. Along the Mahan-Ujjain profile (200 km further east of the present profile), domal structures with a velocity (6.6 km/s) in the upper crust near Narmada river are present (Figs.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations